The Dynamics of Work Quality, Supervision, and Work Environment on Employee Productivity in Barukan Village: A Qualitative Approach - Wahyu Purnomo; Cakra Hidayat; Melinda Astuti (PT. Hidayat Muda Intelektual, 2025)
Employee productivity is an important predictor of organizational performance, especially in rural administrative settings where human resources are minimal. Using a qualitative method, this study investigates the influence of job quality, supervision, and working conditions on employee productivity in Barukan Village. In-depth interviews and theme analysis were used to gather data on the important elements impacting productivity. According to the findings, employees' access to training and resources has a major impact on job quality, but supervision is critical in motivating and improving performance outcomes. Furthermore, the work environment, including infrastructure and culture, has a direct impact on employee engagement and productivity. The report emphasizes the need for better training programs, systematic monitoring, and workplace improvements in order to promote a more productive workforce. Theoretical implications correlate with transformational leadership and Herzberg's Two-Factor Theory, which emphasize intrinsic motivation and participatory leadership as major productivity drivers. Practical ideas include digital transformation, leadership development, and infrastructural improvements to improve rural worker efficiency. This study adds to the greater discussion of rural human resource management and offers policymakers and administrators practical insights. Future research should look at the long-term effects of digitization and leadership techniques on rural workforce performance.